Structural analysis of microRNA-target interaction by sequential seed mutagenesis and stem-loop 3' RACE. - Marc Bohmer; Jutta Sharbati; Jennifer Zur Bruegge; Ralf Einspanier; Soroush Sharbati (PLoS ONE, 2013)
BACKGROUND: As a consequence of recent RNAseq efforts, miRNAomes of diverse tissues and species are available. However, most interactions between microRNAs and regulated mRNAs are still to be deciphered. While in silico analysis of microRNAs results in prediction of hundreds of potential targets, bona-fide interactions have to be verified e.g. by luciferase reporter assays using fused target sites as well as controls incorporating mutated seed sequences. The aim of this study was the development of a straightforward approach for sequential mutation of multiple target sites within a given 3' UTR. METHODOLOGY/PRINCIPAL FINDINGS: The established protocol is based on Seed Mutagenesis Assembly PCR (SMAP) allowing for rapid identification of microRNA target sites. Based on the presented approach, we were able to determine the transcription factor NKX3.1 as a genuine target of miR-155. The sequential mutagenesis of multiple microRNA target sites was examined by miR-29a mediated CASP7 regulation, which revealed one of two predicted target sites as the predominant site of interaction. Since 3' UTR sequences of non-model organisms are either lacking in databases or computationally predicted, we developed a Stem-Loop 3' UTR RACE PCR (SLURP) for efficient generation of required 3' UTR sequence data. The stem-loop primer allows for first strand cDNA synthesis by nested PCR amplification of the 3' UTR. Besides other applications, the SLURP method was used to gain data on porcine CASP7 3'UTR evaluating evolutionary conservation of the studied interaction. CONCLUSIONS/SIGNIFICANCE: Sequential seed mutation of microRNA targets based on the SMAP approach allows for rapid structural analysis of several target sites within a given 3' UTR. The combination of both methods (SMAP and SLURP) enables targeted analysis of microRNA binding sites in hitherto unknown mRNA 3' UTRs within a few days.